Echocardiographic, Biochemical, and Electrocardiographic Correlates Associated With Progressive Pulmonary Arterial Hypertension - Zaky, Ahmed; Zafar, Iram; Masjoan-Juncos, Juan Xavier; Husain, Maroof; Mariappan, Nithya; Morgan, Charity J.; Hamid, Tariq; Frölich, Michael A.; Ahmad, Shama; Ahmad, Aftab (Frontiers in Cardiovascular Medicine, 2021)
Background: Pulmonary arterial hypertension (PAH) is a progressive proliferative vasculopathy associated with mechanical and electrical changes, culminating in increased vascular resistance, right ventricular (RV) failure and death. With a main focus on invasive tools, there has been an underutilization of echocardiography, electrocardiography and biomarkers to non-invasively assess the changes in myocardial and pulmonary vascular structure and function during the course of PAH. Methods: A SU5416-hypoxia rat model was used for inducing PAH. Biventricular functions were measured using transthoracic two-dimensional (2-D) echocardiography/Doppler (echo/Doppler) at disease onset (0 week), during progression (3 weeks) and establishment (5 weeks). Similarly, electrocardiography was performed at 0, 3 and 5 weeks. Invasive hemodynamic measurements and markers of cardiac injury in plasma were assessed at 0, 3 and 5 weeks. Results: Increased RV systolic pressure (RVSP) and rate of isovolumic pressure rise and decline were observed at 0, 3 and 5-weeks in PAH animals. EKG showed a steady increase in QT-interval with progression of PAH whereas P-wave height and RS width were increased only during the initial stages of PAH progression. Echocardiographic markers of PAH progression and severity were also identified. Three echocardiographic patterns were observed: a steady pattern (0-5 weeks) in which echo parameter changed progressively with severity (inferior vena cava (IVC) expiratory diameter and pulmonary artery acceleration time (PAAT)), an early pattern (0-3 weeks) where there is an early change in parameters (RV fractional area change (RV-FAC), transmitral flow, left ventricle (LV) output, estimated mean PA pressure, RV performance index and LV systolic eccentricity index), and a late pattern (3-5 weeks) in which there is only a late rise at advanced stages of PAH (LV diastolic eccentricity index). RVSP correlated with PAAT, PAAT/RV ejection times, IVC diameters, RV-FAC, tricuspid systolic excursion, LV systolic eccentricity and output, and trans-mitral flow. Plasma Myosin light chain (Myl-3) and cardiac troponin I (cTnI) increased progressively across the 3 time points. Cardiac troponin T (cTnT) and Fatty-acid binding protein-3 (FABP-3) were significantly elevated only at the 5-week time point. Conclusion: Distinct electrocardiographic and echocardiographic patterns along with plasma biomarkers were identified as useful non-invasive tools for monitoring PAH progression.